Perspektywa strategiczna w rachunkowości zarządczej. Stan badań naukowych a dydaktyka - Nita, Bartłomiej (Strategic Perspective in Management Accounting. State of Academic Research and Teaching, 2005)
The growing predominance of shareholder wealth creation policy and increasing market competition cause the necessity of taking into account strategic perspective in management accounting. The paper describes the concept of strategic management accounting and on this basis indicates that there is a need for involving this section of accounting as a separate subject into the studies outline at the universities. Main instruments of strategic management accounting were shown in the article and attributed to the particular stages of strategic management: strategy analysis, planning, implementation and strategy control.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 115-129